ANALISIS FATWA DSN-MUI TENTANG AKAD MURABAHAH DALAM PENERAPAN HAK MILIK (BANK SUMUT SYARIAH PERDAGANGAN) - Nazlah Yuningsih (Sekolah Tinggi Agama ISLAM PANCA BUDI PERDAGANGAN, 2023)
The issue of this investigation lies in the Murabahah agreement in the implementation of property rights as regulated in DSN-MUI Fatwa No. 04/DSN-MUI/IV/2000 concerning Murabahah. The Murabahah fatwa states: